The effects of PO43- removal from aqueous solution with varied concentrations of metal oxides in steel slag filter system - Hamdan, Rafidah; Mohd Arshad, Nur Ain Nazirah; Ahmad, Siti Zu Nurain (Penerbit Universiti Sains Malaysia, 2018)
High amount of orthophosphate will accelerate the growth of autotrophs and eutrophication will occur. This phenomenon decreases the water quality and as a result may increase the cost of water treatment for drinking water. The overabundance of orthophosphate occurs when untreated or inadequately-treated wastewater from domestic and industrial activities is released into water bodies. Conventional treatment has been developed to treat wastewater. However, it is not effective for phosphorus removal, hence, high-cost advanced treatment is needed to remove phosphorus. Thus, alternative low-cost treatments for phosphorus removal are needed. Therefore, this study was conducted to understand and investigate the mechanisms of phosphorus removal using two different setups of steel slag filter, Set 1 for high Fe and Set 2 for high Ca. The study was operated at different pH values of 3, 5, 7, 9 and 11 under aerated and unaerated conditions. The samples of steel slag from 12 filters that has been run for three months for each set were semi-quantitatively analysed using scanning electron microscope-energy dispersive X-ray (SEM-EDX) to identify the adsorption of phosphate ion on the surface of the steel slag. The results of SEM-EDX studies showed that adsorption mechanism of phosphate removal takes place on the surface of the steel slag. The precipitates in the steel slag filters were collected and analysed for X-ray diffraction (XRD) for chemical compound identification and the precipitates were confirmed to be Fe3O4, a precursor of iron phosphate related compound.